IMPLEMENTATION OF WARTELPAS BASED ON VIDEO CALL IN THE PANDEMIC COVID-19 - Ejo Imandeka; Noel Tua Lumban Tobing (Polteknik Ilmu Pemasyarakatan, 2020)
The role and function of correctional institutions in providing the rights of prisoners, especially the right to communicate, has become a hot issue during the Covid-19 pandemic. Prisoners who are in correctional institutions / detention demands to be able to communicate with their families, this is a problem considering the face-to-face spread of the virus is prone to occur in overcrowded prisons. Referring to the Instruction of the Director General of Corrections Number: PAS-08.OT.02.02 of 2020 concerning the Prevention, Handling, Control and Recovery of Covid-19, there are efforts to replace the inmates' direct visits with video calls to prevent the spread of COVID-19 in prisons / detention centers. This study analyzes the implementation of video calls as an effort to grant communication rights to prisoners and to prevent the spread of covid-19 in prisons / detention centers.